The Verbal and Non-verbal Signs of “For Women by Women: IDÔLE Lancôme” Advertisement - Ni Made Candra Sandita Dewi; Desak Putu Eka Pratiwi; Ni Wayan Suastini (CV Wahana Publikasi, 2022)
The study is intended to identify the verbal and non-verbal signs used in the advertising “For Women by Women: IDÔLE Lancôme.” Humans employ both verbal and non-verbal communication techniques to engage, including messages, sounds, visuals, and gestures. This study is designed using a descriptive qualitative method. Data is gathered through observation methods. The analysis of verbal and non-verbal signs is done based on Saussure’s semiotic theory. As a result, there are three verbal and three non-verbal signs found. Besides that, the advertiser also wants to provide the audience with a relevant message or piece of advice, emphasizing that ladies should have the courage to follow their vast aspirations. The commercial has nonverbal that may be examined in the form of an image or graphic and appear in terms of color. Through this study, researchers recommend scholars research to explore the vocabulary and grammatical use in advertisements.